Population genetics analysis of Phytophthora nicotianae associated with heart rot in pineapple revealed geneflow between population - Auliana Afandi; Siti Subandiyah; Arif Wibowo; Ayaka Hieno; Afandi AFANDI; Supriyono Loekito; Haruhisa Suga; Koji Kageyama (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Afandi A, Subandiyah S, Wibowo A, Hieno A, Afandi, Loekito S, Suga H, Kageyama K. 2021. Population genetics analysis of Phytophthora nicotianae associated with heart rot in pineapple revealed gene flow between populations. Biodiversitas 22: 3342-3348.  Phytophthora nicotianae has caused heart rot in pineapple. This study identified the population genetic diversity of P. nicotianae, collecting 90 isolates of P. nicotianae from the pineapple plantation sites in three provinces of Indonesia and, as comparisons, seven isolates from non-pineapple sites. Six polymorphic microsatellite markers amplified the non-coding region was used to characterize the population diversity. The phylogenetic tree constructed by MEGA revealed three major clades; the first and second clades were dominated by the isolates from pineapple plantation sites, and the third clade contained isolates from the non-pineapple sites. The allelic pattern analysis using Genalex software revealed the local alleles specific to Lampung and Blitar populations. The AMOVA of microsatellite genotypes data showed that the isolates had a low diversity among the population (6%) but high diversity within individual. Conclusively, P. nicotianae population associated with heart rot in pineapple showed geneflow between populations.